OPTOELECTRONIC DEVICE FOR STRESS DETECTION - A. RAMLAN, NADIA FATIHA (Universiti Teknologi PETRONAS, 2017)
This research study aims to develop a portable, non-invasive stress monitoring system that uses near-infrared light which enables the recording of brain activities during the actual life experience memory task of a subject. This is to clarify the neurophysiological mechanism of stress response by identifying the local hemodynamic changes in human brain. Recent studies have shown that the stress response system able to influence the front part of the brain known as prefrontal cortex. In this paper, a non-invasive near-infrared spectroscopy (NIRs) technology is being studied to design a basic concept of photometric system that allows to monitor and imaging blood oxygenation through skin tissues. The proposed system is applied to human hands as proof of concept. The idea is to ensure that the photometric system can be applied at the forehead area where the level of oxygenation is expected to be higher at rest under mental stress condition. The data will be evaluated as well as the measurement and calculation made by illuminating the right wavelength towards the tissue and detects the reflected light, enabling spatially resolved spectroscopy to be carried out.